2005
DOI: 10.1103/physrevlett.95.137204
|View full text |Cite|
|
Sign up to set email alerts
|

Berry Phase Correction to Electron Density of States in Solids

Abstract: Liouville's theorem on the conservation of phase space volume is violated by Berry phase in the semiclassical dynamics of Bloch electrons. This leads to a modification of the phase space density of states, whose significance is discussed in a number of examples: field modification of the Fermi-sea volume, connection to the anomalous Hall effect, and a general formula for orbital magnetization. The effective quantum mechanics of Bloch electrons is also sketched, where the modified density of states plays an ess… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
295
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(306 citation statements)
references
References 29 publications
6
295
1
4
Order By: Relevance
“…Much of the transport phenomena rely on the Liouville's theorem on the conservation of the phase-space volume element. Recently, [4] Xiao et al observed that, due to the Berry curvature term, the naive phase-space volume form drdk is no more conserved. They attribute this fact to the non-Hamiltonian character of the equations (1)- (2), and suggest to redefine the phase-space density by including a pre-factor,…”
mentioning
confidence: 99%
“…Much of the transport phenomena rely on the Liouville's theorem on the conservation of the phase-space volume element. Recently, [4] Xiao et al observed that, due to the Berry curvature term, the naive phase-space volume form drdk is no more conserved. They attribute this fact to the non-Hamiltonian character of the equations (1)- (2), and suggest to redefine the phase-space density by including a pre-factor,…”
mentioning
confidence: 99%
“…To our best knowledge the statement of Theorem 1 on stationary expectations was used only recently by Gat and Avron [GA03] and later in [XSN05]. As far as we understand, there the statement is taken for granted, but not systematically derived or proved.…”
Section: The Connection One-form a Of The Berry Connection With Respementioning
confidence: 99%
“…This formula for the magnetization in solids is rather recent even on a heuristic level, see [GA03,XSN05]. It was proved by a completely different approach as a special case of a more general formula in [SBT12].…”
Section: The Connection One-form a Of The Berry Connection With Respementioning
confidence: 99%
“…This measure with its √ G modification was originally regarded as "non-canonical" [18], but it is precisely the canonical phase-space volume associated with the unconventional symplectic structure [19].…”
Section: Liouville's Theorem and The Abelian Anomalymentioning
confidence: 99%